Regulation of FGF23 expression in IDG-SW3 osteocytes and human bone by pro-inflammatory stimuli. (5th January 2015) - Ito, Nobuaki; Wijenayaka, Asiri R.; Prideaux, Matthew; Kogawa, Masakazu; Ormsby, Renee T.; Evdokiou, Andreas; Bonewald, Lynda F.; Findlay, David M.; Atkins, Gerald J.
Highlights: Sepsis patients experience transient hypophosphataemia suggesting a role for FGF23. TNF, TWEAK, IL-1β and LPS increased Fgf23 mRNA levels in osteocytes and bone. TNF, TWEAK, IL-1β and LPS suppressed negative regulators of FGF23. TNF and IL-1β caused secretion of C-term FGF23 but not intact FGF23. Inhibition of furin proteases led to intact FGF23 secretion in response to TNF and IL-1β. Abstract: Fibroblast growth factor-23 (FGF23), produced by osteocytes, is the key physiological regulator of phosphate homeostasis. Sepsis patients often experience transient hypophosphataemia, suggesting the regulation of FGF23 levels by pro-inflammatory factors. Here, we used the osteocyte-like cell line IDG-SW3 to investigate the effect of pro-inflammatory stimuli on FGF23 production. In differentiated IDG-SW3 cultures, basal Fgf23 mRNA was dose-dependently up-regulated by pro-inflammatory cytokines TNF, IL-1β and TWEAK, and bacterial LPS. Similar effects were observed in human bone samples. TNF- and IL-1β-induced Fgf23 expression was NF-κB-dependent. Conversely, mRNA encoding negative regulators of FGF23, Phex, Dmp1 and Enpp1, were suppressed by TNF, IL-1β, TWEAK and LPS, independent of NF-κβ signalling. Galnt3, the protein product of which protects intact FGF23 protein from furin/furin-like proprotein convertase cleavage, increased in response to these treatments. C-terminal FGF23 and intact FGF23 protein levels also increased, the latter only in the presence of Furin inhibitors, suggesting that enzymatic cleavage exerts critical control of active FGF23 secretion by osteocytes. Our results demonstrate in principle that pro-inflammatory stimuli are capable of increasing osteocyte secretion of FGF23, which may contribute to hypophosphataemia during sepsis and possibly other inflammatory conditions.